2009
DOI: 10.3168/jds.2009-2380
|View full text |Cite
|
Sign up to set email alerts
|

Feeding barley grain steeped in lactic acid modulates rumen fermentation patterns and increases milk fat content in dairy cows

Abstract: The objectives of the present in vivo and in situ trials were to evaluate whether feeding barley grain steeped in lactic acid (LA) would affect rumen fermentation patterns, in situ dry matter (DM) degradation kinetics, and milk production and composition in lactating dairy cows. The in vivo trial involved 8 rumen-fistulated Holstein cows fed once daily a total mixed ration containing rolled barley grain (27% in DM) steeped for 48 h in an equal quantity of tap water (CTR) or in 0.5% LA (TRT) in a 2 x 2 crossove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
66
3
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 22 publications
11
66
3
1
Order By: Relevance
“…Treating cereals with organic acids may contribute to modulate ruminal tolerance of grain feeding and alleviate the digestive disorders (Iqbal et al, 2009;Humer et al, 2015), thus improving ruminant performance and health. The increased weight gain with a similar feed intake observed in calves fed the TRT diet compared with the CTR diet resulted in a better feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Treating cereals with organic acids may contribute to modulate ruminal tolerance of grain feeding and alleviate the digestive disorders (Iqbal et al, 2009;Humer et al, 2015), thus improving ruminant performance and health. The increased weight gain with a similar feed intake observed in calves fed the TRT diet compared with the CTR diet resulted in a better feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Treating cereals with other organic acids (LA) also decreased starch degradation in the rumen, shifting the digestion of starch to the intestine in dairy cows (Iqbal et al, 2009). Ruminal NH 3 -N concentration was increased with CA-treated barley grain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These VFA observations were made using traditional analytical methods such as GC and HPLC (Iqbal et al 2009). Previous research has indicated that feeding cattle with diets rich in readily degradable carbohydrates, such as barley grain, is associated with increased concentration of VFA in the rumen fluid.…”
Section: Discussionmentioning
confidence: 99%